Positive global mental health: an overview - Jeonghyun Shin; Uriel Halbreich; Dilip V. Jeste (Academia Mental Health & Well-Being)
At present, most healthcare systems are reactive, focusing on symptom control. They over-emphasize impairments, disorders, disabilities, and risk factors, without sufficient attention to individuals’ and communities’ strengths, positive psychosocial characteristics, protective and preventive factors, and the promotion of well-being. This disorder-oriented approach may contribute to a broadening gap between the healthcare service needs of the rapidly increasing urbanized world population and the supply of adequately qualified healthcare providers. It is critical to assess and enhance individuals’ personal strengths, such as resilience, wisdom, optimism, compassion, spirituality, and purpose in life, along with positive social connections and social support. Strong evidence supports the value of positive psychosocial determinants of health, which reduce the risk of mental illnesses, improve the long-term course, and may promote recovery in persons with serious mental illnesses and physical maladies. The primary prevention of mental illnesses can be operationalized. Appropriate strategies should be culturally sensitive, applying interventions that are most appropriate to the local community. Interventions can be informed by the biological similarities in the etiopathology of mental illnesses across the globe, but also by the diverse expressions and varied needs of people from diverse communities. Recent reports of a global behavioral pandemic of loneliness, social isolation, suicides, and drug abuse point to an urgent need for developing therapeutic strategies at both the individual and societal levels to improve the well-being of the general population, including people with mental illnesses. There are potentially exciting examples of such interventions including age-friendly communities, intergenerational activities, and digital interventions to promote positive social connections and social support as well as positive health. It is important for medicine and psychiatry to reduce their primary focus on diseases and risk factors to well-being and health with positive and protective factors.